Investigating the effects of long-term Aroclor 1260 exposure on fatty liver disease in a diet-induced obesity mouse model - Head, Kimberly Z.; Bolatimi, Oluwanifemi E.; Gripshover, Tyler C.; Tan, Min; Li, Yan; Audam, Timothy N.; Jones, Steven P.; Klinge, Carolyn M.; Cave, Matthew C.; Wahlang, Banrida (Frontiers in Gastroenterology, 2023)
Introduction Polychlorinated biphenyls (PCBs) are persistent environmental toxicants that have been implicated in numerous health disorders including liver diseases such as non-alcoholic fatty liver disease (NAFLD). Toxicant-associated NAFLD, also known as toxicant-associated fatty liver disease (TAFLD), consists of a spectrum of disorders ranging from steatosis and steatohepatitis to fibrosis and hepatocellular carcinoma. Previously, our group demonstrated that 12-week exposure to the PCB mixture, Aroclor 1260, exacerbated steatohepatitis in high-fat diet (HFD)-fed mice; however, the longer-term effects of PCBs on TAFLD remain to be elucidated. This study aims to examine the longer-term effects of Aroclor 1260 (>30 weeks) in a diet-induced obesity model to better understand how duration of exposure can impact TAFLD. Methods Male C57BL/6 mice were exposed to Aroclor 1260 (20 mg/kg) or vehicle control by oral gavage at the beginning of the study period and fed either a low-fat diet (LFD) or HFD throughout the study period. Results Aroclor 1260 exposure (>30 weeks) led to steatohepatitis only in LFD-fed mice. Several Aroclor 1260 exposed LFD-fed mice also developed hepatocellular carcinoma (25%), which was absent in HFD-fed mice. The LFD+Aroclor1260 group also exhibited decreased hepatic Cyp7a1 expression and increased pro-fibrotic Acta2 expression. In contrast, longer term Aroclor 1260 exposure in conjunction with HFD did not exacerbate steatosis or inflammatory responses beyond those observed with HFD alone. Further, hepatic xenobiotic receptor activation by Aroclor 1260 was absent at 31 weeks post exposure, suggesting PCB redistribution to the adipose and other extra-hepatic tissues with time. Discussion Overall, the results demonstrated that longer-term PCB exposure worsened TAFLD outcomes independent of HFD feeding and suggests altered energy metabolism as a potential mechanism fueling PCB mediated toxicity without dietary insult. Additional research exploring mechanisms for these longer-term PCB mediated toxicity in TAFLD is warranted.